ANALISIS IMPLEMENTASI BAURAN PEMASARAN JASA UNTUK MENARIK MINAT KONSUMEN MENGGUNAKAN JASA PENGINAPAN GUEST HOUSE GARUDA DI SUNGAI ULIN BANJARBARU - Jumiati; Ilahi , Muhammad Ridho (Scientific : Jurnal Ilmu-Ilmu Sosial dan Ekonomi, 2021)
This study aims to analyze the implementation of the service marketing independent variable consisting of products, prices, promotions, places, people, processes, physical evidence to attract the dependent variable, consumer interest, using the Garuda Guest House accommodation service in Sungai Ulin, Banjarbaru. The analysis was conducted on 70 participants with a sample of 59 people, respondents to a study conducted on Garuda Guest House consumers who are in Sungai Ulin, Banjarbaru, primary data sources are consumers who stay at Garuda Guest House by providing questionnaires to each consumer and secondary data sources is the owner and employee of Garuda Guest House by interview, observation and documentation. Testing is done by descriptive analysis method on the frequency obtained from the SPSS results. The results of this study indicate the 3 most dominant product marketing variables at Garuda Guest House are product variables with indicators of the completeness of room facilities, room cleanliness, room comfort, and spacious rooms. Place variables with conducive location indicators, easy to reach locations, visibility, and parking lots. Price variables with price indicators are more than other prices, affordable prices, prices according to the comfort offered, from prices according to the facilities provided, from these 3 variables that can attract consumers to use accommodation services.